Pemanfaatan Citra Sentinel untuk Pemetaan Perubahan Kerapatan Vegetasi di Desa Jambudipa Kecamatan Cisarua - Astri Indriyani; Adilla Musyafa; Keylila Hanan Zhafrani; Riki Ridwana; Lili Somantri (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2022)
Vegetation is a group of plants, or all plant species found in a given area, with distinct patterns of temporal and spatial distribution. The presence of plants in a certain area helps to maintain the balance of the ecosystem. This study aims to determine the level of vegetation density in Jambudipa Village, Cisarua District, Bandung Regency in 2019 and 2022 using the Resistant Vegetation and Atmospheric Index (MSARVI) method. In 2019 there is still a lot of vegetation, but in 2022 the density will decrease. The amount of vegetation decreases due to several factors, such as the construction of settlements and public facilities such as urban developments and public services, which contribute to the decline in vegetation.